2006
DOI: 10.1002/pmic.200500606
|View full text |Cite
|
Sign up to set email alerts
|

T7 lytic phage-displayed peptide libraries exhibit less sequence bias than M13 filamentous phage-displayed peptide libraries

Abstract: We investigated whether the T7 system of phage display could produce peptide libraries of greater diversity than the M13 system of phage display due to the differing processes of lytic and filamentous phage morphogenesis. Using a bioinformatics-assisted computational approach, collections of random peptide sequences obtained from a T7 12-mer library (X(12)) and a T7 7-mer disulfide-constrained library (CX(7)C) were analyzed and compared with peptide populations obtained from New England BioLabs' M13 Ph.D.-12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 23 publications
1
91
0
Order By: Relevance
“…Another advantage is that T7 phage replicate faster than filamentous phage, which shortens experimental time. A recent study analyzed and compared the sequence diversity of the pre-made M13 phage linear 12-mer and cyclic 7-mer peptide libraries from NEB to the same type of peptide libraries constructed for display on T7 phage using the kit sold by Novagen (Krumpe et al 2006b). Through a bioinformatics-assisted computational approach, the T7 phage libraries were found to have fewer amino acid biases, increased peptide diversity, and more normal distributions of peptide net charge and hydropathy in comparison to the M13 libraries.…”
Section: Lytic Phage Displaymentioning
confidence: 99%
“…Another advantage is that T7 phage replicate faster than filamentous phage, which shortens experimental time. A recent study analyzed and compared the sequence diversity of the pre-made M13 phage linear 12-mer and cyclic 7-mer peptide libraries from NEB to the same type of peptide libraries constructed for display on T7 phage using the kit sold by Novagen (Krumpe et al 2006b). Through a bioinformatics-assisted computational approach, the T7 phage libraries were found to have fewer amino acid biases, increased peptide diversity, and more normal distributions of peptide net charge and hydropathy in comparison to the M13 libraries.…”
Section: Lytic Phage Displaymentioning
confidence: 99%
“…Moreover, Delano et al reported that the Fc-III peptide with an intramolecular disulfide bond can bind to the groove between the CH2 and CH3 domains with high affinity, potentially replacing Protein A binding (7). Krumpe et al reported a T7 phage-displayed peptide library system that showed less bias for amino acids in the displayed peptides and an increased peptide diversity compared to the M13 filamentous phage display (18). Using the T7 phage display system, Sakamoto et al identified a novel IgG-binding peptide ligand which interestingly, recognized acid conformers but not the normal conformation of human IgG (28).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of filamentous phage-displayed peptide library usage may be, in part, due to the initial development of the technology with filamentous bacteriophage, the commercial availability of filamentous phage-displayed peptide libraries or a combination of both or other factors. Recent research in the authors' laboratory indicated that libraries produced with lytic phage could surpass the diversity of filamentous phage-displayed peptide libraries [36]. Peptides displayed on lytic phage do not have to be compatible with host cell synthesis and secretion complexes because lytic phage assembly occurs within the Escherichia coli cytoplasm and mature phage virions are released by cell lysis.…”
Section: Phage-displayed Peptide Library Technologymentioning
confidence: 99%
“…Filamentous phage (M13, f1, and fd) has been the most common vector used in the construction of peptide phage-displayed libraries [31,33,34], although previous studies demonstrated specific and positional amino acid biases in populations of peptides randomly selected from M13 libraries because of the processes of filamentous phage morphogenesis [35,36]. Alternative phage display systems have been developed using lytic phage such as T7, T4, 位 and P4 [37][38][39].…”
Section: Phage-displayed Peptide Library Technologymentioning
confidence: 99%